Primary pulmonary lymphoma in a patient with the acquired immune deficiency syndrome. Issue 5 (May 1989) - Poelzleitner, D; Huebsch, P; Mayerhofer, S; Chott, A; Zielinski, C
Abstract : A case of primary pulmonary lymphoma presenting as a nodular lesion on the chest radiograph in a patient with the acquired immune deficiency syndrome is described.